Indigeneity & Disability: Kinship, Place, and Knowledge-Making - Juliet Larkin-Gilmore; Ella Callow; Susan Burch (Disability Studies Quarterly, 2022)
No abstract available.
Keywords: Kinship; Place; Knowledge-making; Indigenous; ableism; settler colonialism; imperialism; decolonizing; self-determination